Managing Construction Project Constraints: Towards An Integrated Risk Management Hub For Efficient Project Delivery - Buertey, Joseph Ignatius Teye; Doe, David Amedegbe; Atsrim, Felix; Sarfo, Francis (European Journal of Applied Sciences, 2023)
Construction plays a key role as an economic booster in every economy across the globe. Construction projects globally are however plagued by the challenge of systemic risk associated with the project constraints. These varying risks are either overlooked or taken for granted by most project professionals. This research sought to explore project professionals’ perceptions of risk management and examine the extent to which they are integrated into the various processes of construction project management in Ghana. As a quantitative based study, structured questionnaires distributed to the built environment received a response rate of 81%. The data obtained was analysed, using univariate statistical analysis. It was established from the survey that 73% of the respondents did not undertake risk identification and profiling at the initiation stage of the project. It can therefore be held that the concept of risk management being an integral aspect of project planning has therefore not caught up well with the project teams. It was therefore not surprising that even though 81% of the projects included a risk management plan, over 47% of risks unforeseen surfaced during the execution stage. This undoubtedly shows the reason why 91.1% of the projects experienced varying forms of risk during the execution stage. The study again revealed that even though most government-awarded projects (86%) have the challenge of meeting the key project objectives due to scope creep, resulting in schedule overruns and delays in interim payment, most project participants were more particular about delivering the project within budget and governments honouring their payment on time. Although most respondents were aware of the possibility of risk management on the project, the systematic knowledge of managing risk and the forthright application of risk management techniques on construction projects was lacking. This study therefore proposed an all-inclusive risk objective management framework woven around risk education, integration of risk management techniques and broader stakeholder consultation on the subject of risk to equip industry professionals on the subject for the successful delivery of projects.